An Empirical Revision of the Definition of Science Fiction: It Is All in the Techne . . . (October 2020) - Menadue, Christopher Benjamin; Giselsson, Kristi; Guez, David
Researchers employ science fiction and fantasy in public engagement, advocacy, and education as significant sources of insights to identify public interests, inspire public policy, and influence future science. These uses of science fiction as a source that is expected to reflect public interests are undermined if the examples employed by researchers are interpreted differently by the intended audience or beneficiaries of research. We surveyed the public to identify their definitions and discovered a categorization based on clearly defined features. These align with some academic theories but differ from postmodern approaches as the analysis suggests science fiction can be defined categorically. The empirical survey data are consistent and demonstrate an unmistakable distinction between popular definitions of science fiction and fantasy. Our theoretical analysis implies some definitions may be confused by evaluating secondary "fuzzy" characteristics as if they were fundamental features of the genre. We suggest Wittgenstein's family resemblances, between subjects associated with the genre at any specific time, should be interpreted as an ephemeral grouping validated by correlation with enduring core features, rather than definitive. On the basis of the common themes identified from the survey responses and a critique of existing genre models, we suggest the classical concept of techne may best describe the empirical essence of science fiction. Researchers intending to employ science fiction for applications that have an influence in the public realm may wish to consider this when designing their research.